PSII-9 Supplementation with calcium salts from soybean oil in Nellore heifers during gestation leads to proteomic changes on Longissimus thoracis of offspring at slaughter. - Paz, Claudia C P; Queiroz, Amanda C M [UNESP]; Rodrigues, Aline N [UNESP]; Nascimento, Keuven S [UNESP]; Ferreira, Igor M [UNESP]; Abreu, Mateus J I [UNESP]; Vital, Mariana N F [UNESP]; Siqueira, Gustavo R; Resende, Flávio D; Stafuzza, Nedenia B (Oxford University Press (OUP), 2025)
Abstract Maternal supplementation during pregnancy with calcium salts from soybean oil (CSSO), a source of polyunsaturated fatty acids, can modulate gene expression during fetal development that may persist throughout the life of the offspring, affecting their productive performance. Thus, this study aimed to identify differently abundant proteins in the Longissimus thoracis muscle of Nellore offspring in response to supplementation with CSSO during the middle and final thirds of gestation of Nellore heifers. Eighty-two pregnant Nellore heifers (385 ± 49.0 kg body weight) were used in this study at 123 ± 13 days of gestation. All heifers were conceived by fixed-time artificial insemination protocol at 14 and 24 months of age with semen from one bull. The heifers were kept in paddocks with Urochloa brizantha cv. Marandu and were supplemented. The treatments consisted of the complete supplement in the amount of 3 g/kg body weight with CSSO (41 heifers) or without CSSO (41 heifers). After weaning, 24 male calves were selected to compose the growth (10g supplement/kg body weight) and finishing phases (feedlot for 98 days). Samples from L. thoracis muscle were collected during the slaughter to evaluate the meat quality of offspring. Maternal supplementation with CSSO resulted in increased marbling (P < 0.05). A subset of 16 samples (8 with CSSO and 8 without CSSO) were used for proteomic analysis by liquid chromatography coupled to tandem mass spectrometry. The data were processed using the Comet algorithm and the ovine Uniprot database. Data validation and scoring were performed using the Peptide Prophet and Protein Prophet algorithms (FDR ≤ 0.05). Proteins with fold-change ratios ≥ 1.5 and ≤ 0.67 were considered as differentially abundant (P < 0.05). The differentially abundant proteins detected between groups were used to perform functional enrichment analysis by the DAVID tool. Forty-seven differentially abundant proteins were identified between the two experimental groups. Among the differentially abundant proteins, we highlighted those that act in metabolic pathways that contributes to differences observed between treatments, such as cytoskeleton in muscle cells (SUN1, TNNI2, SSPN, MYH1, MYH4, FBN1, ENO2), muscle contraction (TNNI2, MYH1), motor proteins (TUBA8, TNNI2, KIF16B, MYH1), lipid metabolic process (FAH, FUT1, PLCE1), glycerophospholipid metabolism (AGPAT3), metabolism of amino acids and derivatives (AMD1), metabolism of carbohydrates (ENO2), and mineral absorption (TF). Identifying abundant protein changes caused by fetal programming and their roles in critical biological mechanisms to muscle growth and meat quality traits contributes to our understanding of the key mechanisms underlying the effects in the skeletal muscle of Nellore offspring due to maternal supplementation with a source of polyunsaturated fatty acids.